Prevalence and associated factors of malnutrition among indigenous infants in Sepang and Kuala Langat: a cross-sectional study - Low, Sing Wei; Cheong, Ai Theng; Ismail, Irmi Zarina (Academy of Family Physicians of Malaysia, 2026)
Introduction: Malnutrition has emerged as a national issue in Malaysia, especially among indigenous populations. The types of feeding practices affect infantile growth in early life. Detecting malnutrition early and increasing awareness of its contributing factors are critical in handling this issue. This study aimed to determine the prevalence and associated factors of malnutrition among indigenous infants. Methods: This cross-sectional study involved indigenous infants followed up in primary health clinics in Sepang and Kuala Langat, Selangor. Universal sampling was used to recruit participants, where survey interviews and health record reviews were conducted for data collection. Nutritional status was classified based on growth parameters (weight-for-age, height-for-age, BMI-for-age and weight-for-height Z scores) at 2, 4 and 6 months. Any abnormalities were considered to indicate malnutrition. Multiple logistic regression analyses were conducted to determine the associated factors of malnutrition. Results: A total of 119 infants were included in this study. Among them, 45.4%, 44.5% and 10.1% were exclusively breastfed, formula-fed and predominantly breastfed, respectively. Approximately 16.0% had malnutrition at 6 months of age. Multiple logistic regression analysis showed that the male infants had 3.69 and 7.37 times higher odds of having malnutrition and undernutrition than the female infants, respectively. The breastfed infants had 3.46 and 5.10 times higher odds of experiencing malnutrition and undernutrition than the formula-fed infants, respectively. Conclusion: Almost one-fifth of the indigenous infants had malnutrition at 6 months old. The male and breastfed indigenous infants were more at risk for malnutrition. However, these results should be further verified.